Implementasi e-SAKIP dalam Meningkatkan Akuntabilitas Kinerja Organisasi Perangkat Daerah: Studi Kasus pada Kecamatan Asemrowo - Rachmad, Amalia Ramadhani; Priambodo, Bayu (VISA: Journal of Vision and Ideas, 2024)
The Government Agency Performance Accountability System on an electronic basis, often known as e-Sakip, is one of the accountability methods used in Surabaya government organizations. This model is a performance information system based on information and communication technology that makes it easier for government agencies to produce data that can be accessed by the public to inform the performance of government agencies. Because it is web-based, E-Sakip can be accessed by the public anywhere and at any time via the internet. Organisasi Perangkat Daerah (OPD) in the City of Surabaya use the e-Sakip application to fulfill performance accountability, including the Asemrowo District. The aim of this research is to determine the implementation of e-Sakip in improving the accountability of regional organizational performance (case study in Asemrowo District). Researchers used qualitative research methods with a descriptive approach. The data analysis technique used is a research method that uses the concept of policy implementation according to George C. Edward III. The research results found that the implementation of e-Sakip had a positive impact on the accountability of Asemrowo District OPD performance, which was marked by an increase in evaluation results in the last 5 years.